2021
DOI: 10.1177/2151459320987699
|View full text |Cite
|
Sign up to set email alerts
|

Early Outcomes After Surgical Management of Geriatric Patella Fractures

Abstract: Objectives: To report the incidence and risk factors for prolonged hospitalization, discharge to a facility, and postoperative complications in geriatric patients who underwent surgery for patella fracture. Design: Retrospective database review. Setting: The American College of Surgeons—National Surgical Quality Improvement Program (NSQIP) collects data from 600 hospitals across the United States. Patients/Participants: NSQIP patients over 65 years of age with patella fractures. Intervention: Surgical fixation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…The authors concluded that the VTE rates from 2008 to 2016 have remained relatively unchanged and that thromboembolic guidelines should be reassessed. Likewise, Kapilow et al 335 , also published a retrospective review using NSQIP that reported the early outcomes after surgical management of isolated patellar fractures in a population of 1,721 patients 65 years of age or older. Overall, only 13 (0.8%) of these patients developed VTE, but the authors noted that this patient cohort was at higher risk for prolonged hospitalization, discharge to a facility, unplanned readmission or reoperation, and surgical site complications in the first 30 days.…”
Section: -Is Routine Vte Prophylaxis Indicated In Patients With Immob...mentioning
confidence: 99%
See 1 more Smart Citation
“…The authors concluded that the VTE rates from 2008 to 2016 have remained relatively unchanged and that thromboembolic guidelines should be reassessed. Likewise, Kapilow et al 335 , also published a retrospective review using NSQIP that reported the early outcomes after surgical management of isolated patellar fractures in a population of 1,721 patients 65 years of age or older. Overall, only 13 (0.8%) of these patients developed VTE, but the authors noted that this patient cohort was at higher risk for prolonged hospitalization, discharge to a facility, unplanned readmission or reoperation, and surgical site complications in the first 30 days.…”
Section: -Is Routine Vte Prophylaxis Indicated In Patients With Immob...mentioning
confidence: 99%
“…The large cohort studies utilizing the NSQIP database did not control for the routine use of VTE prophylaxis; however, much lower rates of VTE between 0.8 - 0.9% were noted 327,335 . Unfortunately, the NSQIP database does not include VTE prophylaxis, so it is unclear if a prophylaxis was utilized, and if so, what specific type of VTE prophylaxis was used.…”
Section: - Is Routine Vte Prophylaxis Required For Patients With Isol...mentioning
confidence: 99%
“…The overall reoperation rate following surgical treatment of patella fractures has been reported to be 34% [ 12 ]. Increasing co-morbidity is reported to increase the risk of postoperative complications [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%